Bimetallic NiPd/SBA-15 alloy as an effective catalyst for selective hydrogenation of CO2 to methane. (21st May 2019) - Li, Yanping; Zhang, Hui; Zhang, Lianhong; Zhang, Han
Abstract: It is very challenging but still promising to develop highly efficient heterogeneous catalysts for selective hydrogenation of CO2 to methane. Supported bimetallic NiPd/SBA- 15 alloy catalysts with a varied ratio of Ni/Pd were prepared by one-pot wet chemical and impregnation method. A series of techniques were employed to characterize the elemental composition and alloy structure of as-synthesized NiPd/SBA- 15 catalysts. The alloyed bimetallic NiPd/SBA- 15 catalysts showed relatively higher catalytic activity compared with monometallic Pd or Ni-supported SBA- 15 and several other published catalysts. The bimetallic catalyst with Ni:Pd atom ratio of 3:1 was most active in the formation of CH4 and yielded 0.93 mol CH4 per mol CO2 at 430 °C. This superior performance can be attributed to enhanced synergy between Ni and Pd with high dispersion of active sites. Highlights: The NiPd/SBA-15 alloy catalysts were used for CO2 selective hydrogenation to methane. A series of techniques were used to characterize alloy structure of NiPd/SBA-15. Ni0.75 Pd0.25 /SBA- 15 exhibited the highest catalytic performance for the reaction. The excellent activity of Ni0.75 Pd0.25 /SBA-15 can be attributed to synergistic effect.